Risk management and financial stability of banks - Kazbekova, K.M.; Kaldanovna, G.Zh.; Myrzakhanova, D.J.; Davletbayeva, N.B. (Karagandy University of the name of acad. E.A. Buketov, 2022)
Object: Increasing the role of the banking sector in the economy is one of the main tasks of the state. Kazakh-stan’s banking sector is one of the most important sectors of the economy, where the bank acts as a financial institution. Kazakhstan gained considerable success by overcoming the difficult period and achieving its own strategy and tactics of economic reforms after reaching financial stabilization of the peak of structural transformation. Methods: The methods of research, processing and analysis of financial, economic, mathematical, statistical, logi-cal information. Results: The main task of risk management is to minimize the negative impact of risks on the financial results of banks.Justification of the objective need for risk management in banks; identifyingthe importance of risk management in banks and prospects for its development; analysis of data, collected from using statistical methods of data processing and analysis; development of conclusions and recommendations on risk management organization in banks. Conclusions:Risk management identifies the bank management effectiveness, taking into account the factors of uncertainty that may have a negative or positive effect on the bank’s performance. The scientific value of the article is as follows:  specifies the peculiarities of risk management in the bank;  identifies risk management issues in banks and prospects for its development
Тәуекелдерді басқару және банктердің қаржылық тұрақтылығы
Управление рисками и финансовая устойчивость банков
Keywords: risk management; methods; bank; loan portfolio; financial; statistical; model; capital regulation; systemic risk